OPTIMIZATION OF PARAMETERS IN MEWMV AND MEWMA CONTROL CHARTS FOR CLEAN WATER QUALITY CONTROL AT PP KRAKATAU TIRTA GRESIK - Moh. Hafiyusholeh; Hani Khaulasari; Fery Firmansyah; Nurissaidah Ulinnuha (PATTIMURA UNIVERSITY, 2026)
Water is a vital resource whose quality directly affects public health. In Gresik Regency, water treatment processes must be closely monitored, particularly during production. PT PP Krakatau Tirta, a key provider of clean water in the region, plays a strategic role in treating raw water from the heavily polluted Bengawan Solo River. Ensuring that the treated water consistently meets health standards is crucial, highlighting the need for an effective process. This study aims to evaluate the clean water production process and assess the process capability in maintaining the quality of water produced by PT PP Krakatau Tirta Gresik. Laboratory data on key parameters, including pH, dissolved iron, and total dissolved solids, were collected daily from November 25, 2022, to May 31, 2023. These mandatory indicators were analyzed using Multivariate Exponentially Weighted Moving Variance (MEWMV) and Moving Average (MEWMA) control charts to assess process performance. A key contribution of this research lies in optimizing smoothing parameters to enhance control chart performance. Sixteen combinations of (ω,λ) were tested for MEWMV, with the optimal configuration found at (λ = 0.4) and (ω = 0.4), indicating that process variability is statistically stable. For MEWMA, nine values of λ were evaluated, and the optimal weight (λ=0.9) was identified as optimal, yielding a stable process mean after removing two out-of-control points. PT PP Krakatau Tirta, which plays a strategic role in treating raw water from the polluted Bengawan Solo River, was selected as a case study to evaluate the effectiveness of advanced monitoring methods. The results indicate that its clean water production process is well-controlled and capable, with water quality consistently meeting health and safety standards.